Short-term fasting reduces the extent of myocardial infarction and incidence of reperfusion arrhythmias in rats - Snorek, M; Hodyc, D; Sedivý, V; Durišová, J; Skoumalová, A; Wilhelm, J; Neckář, J; Kolář, F; Herget, J (Physiological research, 2012)
The effect of three-day fasting on cardiac ischemic tolerance was investigated in adult male Wistar rats. Anesthetized open-chest animals (pentobarbitone 60 mg/kg, i.p.) were subjected to 20-min left anterior descending coronary artery occlusion and 3-h reperfusion for infarct size determination. Ventricular arrhythmias were monitored during ischemia and at the beginning (3 min) of reperfusion. Myocardial concentrations of beta-hydroxybutyrate and acetoacetate were measured to assess mitochondrial redox state. Short-term fasting limited the infarct size (48.5+/-3.3 % of the area at risk) compared to controls (74.3+/-2.2 %) and reduced the total number of premature ventricular complexes (12.5+/-5.8) compared to controls (194.9+/-21.9) as well as the duration of ventricular tachycardia (0.6+/-0.4 s vs. 18.8+/-2.5 s) occurring at early reperfusion. Additionally, fasting increased the concentration of beta-hydroxybutyrate and beta-hydroxybutyrate/acetoacetate ratio (87.8+/-27.0) compared to controls (7.9+/-1.7), reflecting altered mitochondrial redox state. It is concluded that three-day fasting effectively protected rat hearts against major endpoints of acute I/R injury. Further studies are needed to find out whether these beneficial effects can be linked to altered mitochondrial redox state resulting from increased ketogenesis.
Keywords: Mitochondria; Acetoacetates; 3-Hydroxybutyric Acid; oxidace-redukce; reperfuzní poškození myokardu; Tachycardia, Ventricular; krysa rodu Rattus; mitochondrie; zvířata; infarkt myokardu; Myocardial Reperfusion Injury; potkani Wistar; Rats, Wistar; Male; srdeční arytmie; Myocardial Infarction; Oxidation-Reduction; Rats; komorová tachykardie; Arrhythmias, Cardiac; acetoacetáty; Animals; mužské pohlaví; kyselina 3-hydroxymáselná